2013
DOI: 10.26719/2013.19.7.638
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive use by Iranian women with hypertension, diabetes or obesity

Abstract: Women with chronic medical conditions require careful contraceptive management. The aim of this cross-sectional study in Tehran was to determine the pattern of contraception use by women with diabetes, hypertension or obesity. A sample of 264 women aged 18-53 years old was recruited; 81 (30.7%) had diabetes type 2, 100 (37.9%) were obese/overweight (BMI > 25 kg/m 2 ) and 83 (31.5%) had hypertension. Across all 3 groups, the rate of use of contraceptive methods was significantly different before and after diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…Similar findings and low use of modern contraceptive methods with women mainly using coital withdrawal method were found in Iranian women with type 2 DM, hypertension, or obesity. 15 Although the results of these studies may not be generalizable to different demographic communities, the importance of educating women with DM from all groups of society needs to be emphasized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar findings and low use of modern contraceptive methods with women mainly using coital withdrawal method were found in Iranian women with type 2 DM, hypertension, or obesity. 15 Although the results of these studies may not be generalizable to different demographic communities, the importance of educating women with DM from all groups of society needs to be emphasized.…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence of DM is rising rapidly in the Middle Eastern countries and the developing world, 2 and two studies from Iran have identified low use of contraception by women with DM. 14 , 15 A mixed method cross-sectional study involving 200 women identified many pregnancy-related abnormalities and a lack of confidence in using contraceptives, with many women not using any form of contraception. Similar findings and low use of modern contraceptive methods with women mainly using coital withdrawal method were found in Iranian women with type 2 DM, hypertension, or obesity.…”
Section: Methodsmentioning
confidence: 99%
“…Hasil penelitian White, K., et al (2013) di El Paso (Texas), menemukan 7% pengguna kontrasepsi suntikan dan 10,5% pengguna oral kontrasepsi mengalami hipertensi. Nojomi, M., et al (2013) menemukan 31,5% wanita Iran yang menggunakan kontrasepsi mengalami hipertensi. Murayama, M., et al (2013) yang melakukan penelitian di Thailand juga menemukan bahwa wanita yang menggunakan kontrasepsi pil memiliki tekanan darah lebih tinggi daripada wanita yang tidak pernah menggunakannya.…”
Section: Kataunclassified
“…A limited number of studies explored contraception use among women with diabetes and hypertension. Also, the ndings are inconclusive due to substantial variation in study designs, sample sizes, and the number of chronic conditions as explanatory variables [9][10][11][12][13][14]. Furthermore, patterns of contraception use among women with diabetes and hypertension were not compared with women without such conditions [14].…”
Section: Introductionmentioning
confidence: 99%